KEANEKARAGAMAN PENGALAMAN DEWAN TATA KELOLA PERUSAHAAN TRANSPORTASI INDONESIA - Ilona, Desi (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This study investigates the differences in board experience diversity between transportation companies with high and low growth in Indonesia. Board experience diversity—both at the supervisory board (SBExD) and management board (MBExD) levels—is considered a critical element of corporate governance, influencing strategic decision-making and organizational adaptability. Using a quantitative approach, the study analyzes data from nine publicly listed transportation firms for fourteen years (2004-2017), divided based on company growth performance. Independent samples t-tests reveal no statistically significant differences in SBExD and MBExD between high-growth and low-growth firms, suggesting that board experience diversity may not directly differentiate growth performance in the transportation sector. Effect size analyses also indicate small to negligible practical differences across groups. These findings imply that while board experience diversity remains important for governance quality, its impact may be moderated by other organizational or industry-specific factors. The study highlights the need for broader governance reforms and deeper investigations into contextual variables influencing board effectiveness. Limitations include the reliance on secondary data and cross-sectional design, prompting future research to adopt longitudinal and multi-sectoral approaches to better understand the dynamic role of board diversity in corporate performance.